(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article explores the key benefits of Content and Language Integrated Learning (CLIL) in secondary education. CLIL is an innovative teaching approach that integrates foreign language learning with academic content, allowing students to develop both linguistic and cognitive skills simultaneously. The paper highlights how CLIL enhances language competence, promotes higher-order thinking, increases student motivation, and prepares learners for global communication. Furthermore, it discusses challenges teachers face in implementing CLIL, such as balancing content and language objectives, and offers practical recommendations to overcome these issues through professional training and collaboration. Overall, CLIL proves to be an effective method for developing globally minded, competent, and motivated learners